Recent acquisitions : Autumn 1988. - Gallery Willy D'Huysser, Brussel (Brussels : Gallery Willy D'Huysser, 1988)
Delvaux, Paul ; Ubac, Raoul ; Mortier, Antoine ; Degottex, Jean ; Soulages, Pierre ; Wyckaert, Maurice ; Dubuffet, Jean ; Bettencourt, Pierre ; Appel, Karel ; Alechinsky, Pierre ; etc.
Recent acquisitions : Autumn 1988, Gallery Willy D'Huysser, Brussels, 1988
boek